AUDIOVISUAL TRANSLATION ON PORTUGUESE NEWS BULLETINS - Menezes, Rita (2019)
The daily access to news broadcast is something that, generally speaking, we do not abstain ourselves from, whether it is to be aware of what is going on in our country or to be informed about international events. But are we attentive to how the information about those events, namely those that occur outside Portugal, reaches us? How is that information handled – and who handles it – until we have it at our disposal? Is the audience aware that a large part of the news must be translated and must have a linguistic treatment? And how can we describe that same translation and the way it is presented? This case study is just an example of translation’s role and its crucial presence on TV news broadcast, considering the way translation is processed, how it is barely noticed – or not –, how it influences the construction of the story and how the story influences the translation process. This case study was presented at the 2nd International Conference “Media for All”, with the theme “Text on Air, Text on Screen”, which took place at the Polytechnic Institute of Leiria, on 7-9 November 2007.